A risk assessment of dietary Ochratoxin a in the United States. (February 2017) - Mitchell, Nicole J.; Chen, Chen; Palumbo, Jeffrey D.; Bianchini, Andreia; Cappozzo, Jack; Stratton, Jayne; Ryu, Dojin; Wu, Felicia
Abstract: Ochratoxin A (OTA) is a mycotoxin (fungal toxin) found in multiple foodstuffs. Because OTA has been shown to cause kidney disease in multiple animal models, several governmental bodies around the world have set maximum allowable levels of OTA in different foods and beverages. In this study, we conducted the first exposure and risk assessment study of OTA for the United States' population. A variety of commodities from grocery stores across the US were sampled for OTA over a 2-year period. OTA exposure was calculated from the OTA concentrations in foodstuffs and consumption data for different age ranges. We calculated the margin of safety (MOS) for individual age groups across all commodities of interest. Most food and beverage samples were found to have non-detectable OTA; however, some samples of dried fruits, breakfast cereals, infant cereals, and cocoa had detectable OTA. The lifetime MOS in the US population within the upper 95% of consumers of all possible commodities was >1, indicating negligible risk. In the US, OTA exposure is highest in infants and young children who consume large amounts of oat-based cereals. Even without OTA standards in the US, exposures would not be associated with significant risk of adverse effects. Highlights: OTA, a mycotoxin found in many foods and drinks, is linked to kidney disease. OTA levels in food and drinks gathered from grocery stores across the US were low. Worst-case scenarios for OTA exposure were assessed by age group and diet. OTA exposure is highest for infants, due to oat-based cereals and low bodyweight. US lifetime disease risk estimates for worst cases of OTA exposure are negligible.